Social capital and oral health: The association of social capital with edentulism and chewing ability in the rural elderly. (January 2018) - Kim, Eun-Kyong; Jung, Yun-Sook; Kim, Kyung-Hee; Kim, Ki-Rim; Kwon, Gi-Hong; Choi, Youn-Hee; Lee, Hee-Kyung
Highlights: We visited the house of elderly and assessed social capital, edentulism, and chewing ability. Chewing ability was assessed objectively using gum that changed color based on chewing performance. Poor social network is associated with poor chewing ability in the elderly living in rural area. Abstract: Objective: The association between social capital and oral health had been reported in various ways, but still remains unclear. We investigated the association between the social capital of the elderly living in a rural region and their edentulism and chewing ability. Methods: A total of 241 elderly aged ≥ 70 years living in a rural city of Korea participated in this cross-sectional study. Their social capital was surveyed by questionnaire assessing its network and trust dimensions. Their edentulism and chewing ability were assessed by oral examination and chewing gum whose color changes based on the mastication performance. Results: The mean age of the participants was 82.7 (ranged 71 to 101) years and 68.8% of them were female. In the binomial regression analysis, the general network aspect of the network dimension was significantly associated with chewing ability, of which the prevalence ratio was 1.88 (95% CI: 1.16-3.06) in the age, sex, education and marital status-adjusted model. Conclusion: Our findings suggest that social capital, such as a poor social network, is associated with poor chewing ability in the elderly living in rural areas.